China’s Democratization Revisited - Day , Dong-Ching (Advances in Social Sciences Research Journal, 2021)
When the Tiananmen Incident happened and the Berlin Wall collapsed in 1989 that indicated the end of the Cold War, some scholars predicted that China’s democratization would be realized in the short term. However, China not only didn’t become a democratic country, but also overtook Japan as the world number two economy in 2010; probably it will replace US as the world number one economy in 2030 which highly challenge the theory of economic growth bringing democratization. How come modernization theory doesn’t apply to China case after its rapid economic growth for decades? The easiest way to argue why China hasn’t become democratic country based on theories of democratization is that they couldn’t fit into China’s special situation. If that is the case, then further question will be why China’s situation is so special and what are behind it. This paper is trying to explain why China hasn’t democratized from the perspective of identity, and elaborate that ‘Four insistences’, ‘Being bullied experiences’, and ‘Democracy’s disorder and China model’ are those factors enhancing China’s identity. If those factors don’t change, it is hard to see China democratization happening in the foreseeable future.